You say you want a revolution?: Radical idealism and its tragic consequences - Chirot, Daniel (Princeton University Press, 2020)
Frontmatter -- Contents -- Acknowledgments -- 1. Revolution as Tragedy -- 2. Incompetence, Chaos, and Extremism -- 3. Reaction, War, Invasion, and Revolutionary Terror -- 4. The Tyranny of Idealistic Certitude and Imagined Utopias -- 5. Revolutions Betrayed -- 6. Peaceful Revolutions? -- 7. Are There Lessons for Us to Learn? -- Notes -- Index of Cited Authors